CANDI BENTAR MONUMEN RELIGIUS HINDU (Suatu Kajian Historis Teologis) - Dharmawan, I Gusti; Wijayanti, Ni Putu Sri; Wiguna Murti, I Wayan Indra (Fakultas Dharma Duta dan Brahma Widya, 2024)
Hindus construct holy places (pura) to symbolize Mount Mahameru, the highest mountain in Indonesia. These temples represent Mount Kailasa (Kailas), the abode of Bhatara Shiva (the Supreme God). Each temple typically features a